2020
DOI: 10.3390/s20113076
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the RSSI Long-Term Data of a WSN for the RF Channel Modeling in EPS Environments

Abstract: In this paper, we propose a methodology to use the received signal strength indicator (RSSI) available by the protocol stack of an installed Wireless Sensor Network (WSN) at an electric-power-system environment (EPS) as a tool for obtaining the characteristic of its communication channel. Thereby, it is possible to optimize the settings and configuration of the network after its deployment, which is usually run empirically without any previous knowledge of the channel. A study case of a hydroelectric power pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Only three nodes are used as sensor nodes, and the rest are used as pure routers. The radios were deployed on a 92 m × 78 m area covering the barrage, the central building, and where the step-up transformers and high-voltage cables are present [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…Only three nodes are used as sensor nodes, and the rest are used as pure routers. The radios were deployed on a 92 m × 78 m area covering the barrage, the central building, and where the step-up transformers and high-voltage cables are present [50,51].…”
Section: Methodsmentioning
confidence: 99%
“…Positioning and localization based on the received signal strength indicator (RSSI) is found to be an effective way to determine the location. A path loss model, which can be implemented by path loss exponent (PLE) in association with data location, can provide more accurate position estimations using RSSI [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies proposed the use of RSSI both in its instantaneous capacity as an indicator of repetitive patterns and as a long term accumulative measurement to enable optimization of power networks by modifying the communication channel settings, which showed that RSSI can be effectively used to optimize network characterisitics in a WSN [33].…”
Section: Introductionmentioning
confidence: 99%